The Relationship Between Mothers’ Knowledge and Attitudes Toward Reproductive Health Preparedness in Disaster Situations in East Polongbangkeng District, Takalar Regency, 2026 - Ruqaiyah Ruqaiyah; Noviyani Hartuti; Yoan Putri Praditia Susanto; Asyima Asyima; Fatmawati Amir; Basuki Rahmat MS; Sahabuddin Sahabuddin; Ayatullah Harun (International Journal of Health and Social Behavior, 2026)
Women’s reproductive health is a particularly vulnerable aspect of well-being in disaster situations, making maternal preparedness essential for minimizing health risks. This study aims to analyze the relationship between mothers’ knowledge and attitudes toward reproductive health preparedness in disaster situations in East Polongbangkeng District, Takalar Regency, 2026. A quantitative observational analytic design with a cross-sectional approach was employed. A total of 117 mothers were recruited as respondents based on established inclusion criteria. Data were collected using validated and reliable questionnaires and analyzed through univariate and bivariate analyses using the chi-square test at a significance level of α = 0.05. Results showed that the majority of respondents had good knowledge (82.1%), good attitudes (94.0%), and good preparedness (78.6%). Statistically significant associations were found between mothers’ knowledge and reproductive health preparedness (p = 0.003), and between mothers’ attitudes and reproductive health preparedness (p = 0.037). It is concluded that better maternal knowledge and attitudes are associated with better reproductive health preparedness in disaster situations. Health centers and healthcare workers are recommended to strengthen community-based reproductive health preparedness education and promotion in disaster-prone areas.